2002
DOI: 10.1094/cchem.2002.79.4.567
|View full text |Cite
|
Sign up to set email alerts
|

Creep‐Recovery of Wheat Flour Doughs and Relationship to Other Physical Dough Tests and Breadmaking Performance

Abstract: Cereal Chem. 79(4):567-571Measurements of creep-recovery of flour-water doughs were made using a dynamic mechanical analyzer (DMA) in a compression mode with an applied probe force of 50 mN. A series of wheat flour and blend samples with various breadmaking potentials were tested at a fixed water absorption of 54% and farinograph optimum water absorption, respectively. The flour-water doughs exhibited a typical creep-recovery behavior of a noncross-linked viscoelastic material varying in some parameters with f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
88
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(106 citation statements)
references
References 17 publications
15
88
0
3
Order By: Relevance
“…In addition, when the HPMC content was modified, it hardly affected the compliance values and there were no changes observed in the bread specific volume. Other authors also found a good correlation between maximum recovery strain and bread volume for commercial wheat flour (Wang and Sun, 2002) and pure wheat cultivars (Van Bockstaele et al, 2008) that differed in quality.…”
Section: Gluten-free Bread Qualitymentioning
confidence: 78%
“…In addition, when the HPMC content was modified, it hardly affected the compliance values and there were no changes observed in the bread specific volume. Other authors also found a good correlation between maximum recovery strain and bread volume for commercial wheat flour (Wang and Sun, 2002) and pure wheat cultivars (Van Bockstaele et al, 2008) that differed in quality.…”
Section: Gluten-free Bread Qualitymentioning
confidence: 78%
“…The improved batter film stability would prevent premature gas cell rupture and collapsing of dough during proofing and oven spring, explaining the increases in maximum height obtained with LAC 0.1 and PR 0.01 supplementation. High correlation between maximum recovery and loaf volume were reported for wheat flour breadmaking (Wang & Sun, 2002). It can be suggested that the increase in softness, deformability and elasticity of LACand PR-treated batters are responsible for the improved breadmaking performances of the oat flour.…”
Section: Discussionmentioning
confidence: 95%
“…Control 1 Dexter, Scanlon, & Cenkowski, 1999;Salvador, Sanz, & Fiszman, 2006;Uthayakumaran, Newberry, Phan-Thien, & Tanner, 2002;Wang & Sun, 2002). Batches (500 g) were mixed in a 6 quart Kitchen Aid mixer 600 Series (Hobart Co., Troy, OH) with paddle attachment at speed 4 for 5 min and allowed to rest in sealed containers for 30 min to allow adequate time for hydration of the gums in the dough systems before all testing.…”
Section: Formulationsmentioning
confidence: 99%